At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Answer:
x² + y² - 12x - 6y + 29 = 0
Step-by-step explanation:
Simplifying the equation using (a + b)² = a² + 2ab + b²:
(x - 6)² + (y - 3)² = 16
⇒ [x² - 2(x)(6) + 6²] + [y² - 2(y)(3) + 3²] = 16
⇒ [x² - 12x + 36] + [y² - 6y + 9] = 16
⇒ x² - 12x + 36 + y² - 6y + 9 = 16
General form of a circle = x² + y² + Cx + Dy + E = 0
Before we reorganize the equation in general form, we need to have the R.H.S as 0. For that, we need to subtract 16 both sides.
Subtract 16 both sides:
⇒ x² - 12x + 36 + y² - 6y + 9 = 16
⇒ x² - 12x + 36 + y² - 6y + 9 - 16 = 16 - 16
⇒ x² - 12x + 20 + y² - 6y + 9 = 0
Reorganizing the equation in general form:
x² - 12x + 20 + y² - 6y + 9 = 0
⇒ x² - 12x + 20 + y² - 6y + 9 = 0
⇒ x² + y² - 12x + 20 - 6y + 9 = 0
⇒ x² + y² - 12x + 20 - 6y + 9 = 0
⇒ x² + y² - 12x - 6y + 20 + 9 = 0
⇒ x² + y² - 12x - 6y + 29 = 0
Thus, the equation in general form is x² + y² - 12x - 6y + 29 = 0.
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.